Changes in Resting fMRI Networks in Patients with Severe Traumatic Brain Injury During Therapeutic Rhythmic Transcranial Magnetic Stimulation (Case Report) - A. S. Zigmantovich; E. V. Sharova; M. М. Kopachka; A. S. Smirnov; E. V. Alexandrova; Yu. V. Kotovich; Ya. I. Deza-Araujo; M. V. Stern; E. M. Troshina; I. N. Pronin (Общая реаниматология, 2022)
Severe traumatic brain injury (TBI) accompanied by impaired consciousness manifesting as prolonged postcoma unawareness (PCU) is one of the current medical and social problems causing high morbidity and mortality worldwide. Difficult recovery of such patients necessitates the development of additional neurorehabilitation approaches, including neuromodulation methods, as well as the search for objective markers of treatment efficacy.   Aim of the study: to evaluate the effect of therapeutic rhythmic transcranial magnetic stimulation (rTMS) on fMRI resting state networks (RSN) in PCU after severe TBI.   Materials and Methods. We analyzed individual fMRI RSN in three patients with PCU before and after a course of rTMS performed at different timepoints after severe TBI and with different efficacy of treatment. We assessed the topography and quantitative characteristics of the networks (DMN, sensorimotor, control functions, left and right fronto-parietal, auditory, and speech) known to be most significant for recovery of consciousness.   Results. We found a trend toward normalization of RSN topography as well as an increase in the integral index of network intensity in two of three patients with a distinct increase in consciousness after a course of rTMS.   Conclusion. Using case observations, we have demonstrated the therapeutic efficacy of rTMS and feasibility of using fMRI RSN as a reliable diagnostic approach in PCU following severe TBI.